PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYELUNDUPAN BARANG ELEKTRONIK DI WILAYAH KABUPATEN KEPULAUAN MERANTI - Pandapotan Uli Sitorus; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Smuggling in essence can be interpreted as an act of approving, conducting,sending, goods with not fulfilling the applicable laws and regulations, or notfulfilling customs formalities stipulated by law. First, law enforcement carried outby Customs and Excise PPNS on electronic goods smuggling, Second, Factors notcarried out investigations, Third, Law Enforcement carried out by PPNS is inaccordance with legislation.This research is sociological legal research that is research that wants to seethe unity between law and society with the gap between das sollen and das sein.This research was conducted in the customs area of the long strait excise law,while the population and samples were all parties involved in the problemexamined in this study, the data sources used, primary data, and secondary data,data collection techniques in this study were conducted through interviewingliterature review and questionnaireThe conclusion of this study is First the actions taken by Customs and ExcisePPNS to eradicate smuggling of electronic goods, namely in the form ofpreventive and repressive law enforcement. Preventive law enforcement, namelyobservation and patrol, repressive law enforcement, namely making arrests andseizures. The second causes the absence of an investigation into the alleged crimeof smuggling electronic goods is evidence that has been destroyed before theinvestigation is carried out. Third, law enforcement for smuggling of electronicgoods by PPNS has not been in accordance with the laws and regulations becausethe goods from the capture have been destroyed before investigation.The author's advice on the problems examined is First the Customs andExcise strait provides an understanding of the impact of electronic goods. Bothinvestigations on electronic goods smuggling must be in accordance with legalprocesses in accordance with the criminal justice system in Indonesia. Customsand Excise on electronic smuggling in Meranti island districts must be carried outin accordance with applicable provisions of the customs lawKeywords: Law Enforcement-Crime Electronic smuggling